Mathematical Modeling in Tumor Growth using Gompertz Model - Taib, Siti Farzana; Dr Syahira binti Mansur, (Enhanced Knowledge in Sciences and Technology, 2022)
This project focuses on how differential equation to help provide the mathematical model of tumor growth by using Gompertz model. The Gompertz model is used to analyse the growing glioblastoma (brain tumor) data in order to determine how accurate the growth over time outcomes are. The tumor data is graphed in Excel alongside the values from the Gompertz equation. The Excel solver is used to determine the constant values of  ,  and . The data from the tumor closely resembles the outcome of the Gompertz model with sigmoidal “S” curve.